Usefulness of WhatsApp in the Process of English Language Learning among Undergraduate Students: A Perception Study - Hanif, Nadia; Sajid , Maria (Journal of Communication and Cultural Trends, 2019)
Technology has invaded the field of education and has become a major source of gaining and spreading knowledge. Among the various technological advancements currently facilitating teaching and learning in several educational disciplines, mobile technology is noteworthy. These days, almost all students keep a mobile phone and use its applications for different purposes. With the integration of technology in education, mobile devices are also being incorporated in numerous educational disciplines including language learning. This research was carried out to study students’ perception of the impact of WhatsApp in learning English language. A questionnaire of 27 items was administered to find out the perception of 157 students about the impact of WhatsApp in English language learning. Students’ access to internet was also explored to study the influence of the availability of internet on students’ perception. The findings showed that students have a positive perception of the influence of WhatsApp in English language learning. They believe that using WhatsApp for language learning gives them confidence, improves their English language knowledge and enhances their four language skills. They also gave a positive response about the ubiquitous use of WhatsApp and their preference of using WhatsApp as compared to other teaching and learning pedagogies.